Legionella longbeachae effector protein RavZ inhibits autophagy and regulates phagosome ubiquitination during infection. - Yunjia Shi; Hongtao Liu; Kelong Ma; Zhao-Qing Luo; Jiazhang Qiu (PLoS ONE, 2023)
Legionella organisms are ubiquitous environmental bacteria that are responsible for human Legionnaires' disease, a fatal form of severe pneumonia. These bacteria replicate intracellularly in a wide spectrum of host cells within a distinct compartment termed the Legionella-containing vacuole (LCV). Effector proteins translocated by the Dot/Icm apparatus extensively modulate host cellular functions to aid in the biogenesis of the LCV and intracellular proliferation. RavZ is an L. pneumophila effector that functions as a cysteine protease to hydrolyze lipidated LC3, thereby compromising the host autophagic response to bacterial infection. In this study, we characterized the RavZ (RavZLP) ortholog in L. longbeachae (RavZLLO), the second leading cause of Legionella infections in the world. RavZLLO and RavZLP share approximately 60% sequence identity and a conserved His-Asp-Cys catalytic triad. RavZLLO is recognized by the Dot/Icm systems of both L. pneumophila and L. longbeachae. Upon translocation into the host, it suppresses autophagy signaling in cells challenged with both species, indicating the functional redundancy of RavZLLO and RavZLP. Additionally, ectopic expression of RavZLLO but not RavZLP in mammalian cells reduces the levels of cellular polyubiquitinated and polyneddylated proteins. Consistent with this process, RavZLLO regulates the accumulation of polyubiquitinated species on the LCV during L. longbeachae infection.